A New Method for Solving Three Moment Equation in Well Trajectory Control - Xi, Jiangjun; Li, ZhuangWei; Tao, Lin; Li, Wenlong; Jin, Nan; Wang, Yufeng (Chemistry and technology of fuels and oils, 2024)
Considering the assembly as a multi-span, continuous beam-column, a system of “three moment equations” can be derived to compute side force components as well as all reactive forces, deflection, bending moment, and slope. Solving high-order nonlinear equations involves programming and debugging, which can be time-consuming. Moreover, many methods for solving such equations may not necessarily yield correct results. However, the Python open-source library “sympy” simplifies this process by eliminating the need for complex programming and debugging. It only requires the necessary equation information to quickly solve the high-order nonlinear equations. Additionally, C# provides the capability to rapidly create graphical user interfaces, enhancing the solution’s usability. By utilizing Python.NET to call Python code, it reduces the programming workload and effectively addresses the problem of solving a system of three moment equations.